Genomic resources for a unique, low-virulence Babesia taxon from China. Issue 1 (December 2016) - Guan, Guiquan; Korhonen, Pasi; Young, Neil; Koehler, Anson; Wang, Tao; Li, Youquan; Liu, Zhijie; Luo, Jianxun; Yin, Hong; Gasser, Robin
Abstract Background Babesiosis is a socioeconomically important tick-borne disease of animals (including humans) caused by haemoprotozoan parasites. The severity of babesiosis relates to host and parasite factors, particularly virulence/pathogenicity. AlthoughBabesia bovis is a particularly pathogenic species of cattle, there are species ofBabesia of ruminants that have limited pathogenicity. For instance, the operational taxonomic unitBabesia sp. Xinjiang (abbreviated here asBx ) of sheep from China is substantially less virulent/pathogenic thanB. bovis is in cattle. Although the reason for this distinctiveness is presently unknown, it is possible thatBx has a reduced ability to adhere to cells or evade/suppress immune responses, which might relate to particular proteins, such as the variant erythrocyte surface antigens (VESAs). Results We sequenced and annotated the 8.4 Mb nuclear draft genome ofBx and compared it with those ofB. bovis andB. bigemina by synteny analysis; we also investigated the genetic relationship ofBx with selectedBabesia species and related apicomplexans for which genomic datasets are available, and explored the VESA complement inBx . Conclusions The availability of theBx genome now provides unique opportunities to elucidate aspects of the molecular biology, biochemistry and physiology ofBx, and to explore the reason(s) for its limited virulence and/or apparent ability to evade immune attack by the host animal. Moreover, the present genomic resource and anin vitro culture system forBx raises the prospect of establishing a functional genomic platform to explore essential genes as new intervention targets against babesiosis.